Compensation of orbital-angular-momentum multiplexed communication system with wavefront correction - Li ZOU; Le WANG; Shi-bing ZHANG; Sheng-mei ZHAO (Tongxin xuebao)
It was shown that the quality of free-space optical communication system using OAM(orbital angular momentum)multiplexing was inevitably degraded by AT(atmospheric turbulence).A wavefront phase correction based on Gerchberg-Saxton algorithm to mitigate the wave front phase distortion of the OAM-multiplexed system transmitting through AT was proposed.The simulation results show that the crosstalk caused by AT decreases by using the proposed scheme.When the refractive index structure constant of AT <msubsup> C n 2 </msubsup> is lower than 2＆#x00D7; 10 ＆#x2212;15 m ＆#x2212; 2 3 ,the BER(bit error rate)performance is decreased by two or three orders of magnitude with the proposed scheme.